A motor function for the DEAD-box RNA helicase, Gemin3, in Drosophila. - Ruben J Cauchi; Kay E Davies; Ji-Long Liu (PLoS Genetics)
The survival motor neuron (SMN) protein, the determining factor for spinal muscular atrophy (SMA), is complexed with a group of proteins in human cells. Gemin3 is the only RNA helicase in the SMN complex. Here, we report the identification of Drosophila melanogaster Gemin3 and investigate its function in vivo. Like in vertebrates, Gemin3 physically interacts with SMN in Drosophila. Loss of function of gemin3 results in lethality at larval and/or prepupal stages. Before they die, gemin3 mutant larvae exhibit declined mobility and expanded neuromuscular junctions. Expression of a dominant-negative transgene and knockdown of Gemin3 in mesoderm cause lethality. A less severe Gemin3 disruption in developing muscles leads to flightless adults and flight muscle degeneration. Our findings suggest that Drosophila Gemin3 is required for larval development and motor function.